Green Banking, Earning Per Share and Company Value - Agustina, Sri; Holiawati, Holiawati; Khotimah, Maryatus Kusnul; Adhania, Safira (EAJ (Economic and Accounting Journal), 2023)
This study aimed to determine the effect of the implementation of green banking and earnings per share on the company's value. This study uses a sample of banking companies listed on the IDX during 2019-2021. The sampling technique used is purposive sampling. The sample is 15 banks, using panel data regression analysis and statistical tools Eviews.12. the study results indicate that green banking and earnings per share simultaneously affect the company's value. While partially green banking does not affect firm value and earnings per share positively and significantly, affect firm value. This study uses a rarely studied independent variable, namely green banking. The novelty of this study is that green banking is calculated by adding green banking indicators.